USING VIDEO TO IMPROVING LISTENING COMPREHENSION OF FOURTH GRADE STUDENTS - Vina Anggia Nastitie Ariawan; Endah Sulistyani (IKIP Siliwangi, 2020)
This research aims to test the effect of video on the listening skill of fourth-grade students. The research used a quasi-experimental method with a non-equivalent control group design. Therefore, the populations were fourth-grade students of Ggugus Dewi Sartika Majenang and the sample of this research based on a purposive sampling technique. In addition, the research sample was selected by two schools with the same number and characteristics of students. Furthermore, the data collection technique used a listening skill test. Before carrying out the research, the researchers conducted a test of listening skills to be tested for validity and reliability. The results of the validity test showed if the question of the listening skill test in the valid category. The students did a listening skill test and the result was analyzed using inference statistics. The results of the research indicated that students who were treated with video had better listening skills than students who were not treated. Moreover, the researcher concludes that the video had an effect on the listening skill of fourth-grade students.